EVALUASI KINERJA SIMPANG TIGA BERSINYAL JALAN SUDIRMAN – JALAN TUANKU TAMBUSAI PEKANBARU - Parada Afkiki Eko Saputra (Universitas Quality, 2018)
Sudirman Street intersection is part of the main road in the city of Pekanbaru where the activity in this road area is quite besar.ruas this road is a transportation path that is used by the community if they want to head office and school in Pekanbaru city. Thus, it is often delayed because the volume of vehicles passing through the intersection especially from the west (Jalan Tuanku Tambusai) is quite dense, resulting in slowing and accelerating vehicles that veer at intersections and can cause conflicts from other vehicles that cross the intersection. Prior to the first research, measurements were taken to collect the width of the approach data on the intersection. The data taken were all vehicles passing through the intersection of either the left, straight, or right turn, and the length of the queue. The research was conducted for three days on Saturday (05/30/2011), Monday (02/05/2011), with the morning observation hour (06.00-08.00) WIB, noon (12:00 to 14:00 pm ), afternoon at (16.00-18.00). The data is then processed by Method MKJI 1997. Based on the evaluation that has been done, the length of queue and degree of saturation at the intersection is very high. To overcome this, three alternative designs are green time design, road geometry design, and road geometry design along with green time design. The result of the calculation after 3 alternatives shows that the degree of saturation in each approach has met the acceptable value of 0.75. The right handling solution done today is with the green time design alternative.